Study of Electrolyte and Electrode Composition Changes vs Time in Aged Li-Ion Cells. Issue 2 (19th February 2021) - Thompson, L. M.; Harlow, J. E.; Eldesoky, A.; Bauer, M. K. G.; Cheng, J. H.; Stone, W. S.; Taskovic, T.; McFarlane, C. R. M.; Dahn, J. R.
Abstract : Many studies of Li-ion cells examine compositional changes to electrolyte and electrodes to determine desirable or undesirable reactions that affect cell performance. Cells involved in these studies typically have a limited test lifetime due to the resource intensive and time-consuming nature of these experiments. Here, electrolyte and electrode analyses were performed on a large matrix of cells tested at various conditions and with various cycle lifetimes. The matrix included LiNi0.5 Mn0.3 Co0.2 O2 (NMC532)/graphite and LiNi0.6 Mn0.2 Co0.2 O2 (NMC622)/graphite pouch cells with excellent performing electrolyte mixtures, both cycling and storage protocols at 40 °C and 55 °C with both 4.3 V and 4.4 V upper cutoff potentials. This study presents post-test analysis (electrochemical impedance spectroscopy, differential voltage analysis, differential thermal analysis), electrolyte analysis (gas chromatography, quantitative nuclear magnetic resonance), and electrode analysis (micro X-ray fluorescence) for these cells after 3, 6, 9, and 12 months of testing. Many products and reactants, such as fraction of transesterification, gas production, transition metal dissolution appeared to have a constant rate of increase in this 12-month observation period. In most cases, results from cells after 3 to 6 months of testing could be used to reasonably estimate the status of the cells (electrolyte composition, gas production, transition metal dissolution) at 12 months.